The Influence of Digital Marketing Strategies on Consumer Purchase Decisions - Yusniati Sihombing; Safna Deviputri Suwandy; Morgan Nicolas Sitorus; Muhammad Saeful Haddy; Baron (Journal of Entrepreneurial and Business Diversity, 2025)
Purpose:The rapid growth of digital technology has significantly transformed marketing practices and consumer behavior. Businesses increasingly rely on digital marketing strategies to communicate value, engage customers, and influence purchasing decisions. This study aims to examine the effect of digital marketing strategy on consumer purchase decisions. Methodology:The research employed a quantitative explanatory approach with data collected from 100 respondents who have experience purchasing products through digital platforms. Data were gathered using a structured questionnaire measured on a five-point Likert scale. The analysis techniques included validity and reliability tests, classical assumption testing, simple linear regression, t-test, and coefficient of determination (R²). Findings:The results indicate that digital marketing strategy has a positive and significant effect on consumer purchase decisions, with a regression coefficient of 0.645 and a significance value of 0.000 (< 0.05). The coefficient of determination shows that digital marketing strategy explains 43.3% of the variance in consumer purchase decisions, while the remaining 56.7% is influenced by other factors. These findings suggest that effective digital marketing strategies play an important role in shaping consumer decision-making processes.Implication:The study provides practical insights for businesses to optimize digital marketing activities to improve customer engagement and purchasing outcomes.